1970
DOI: 10.3329/bjb.v37i2.1733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on ion accumulation in maize (<i>Zea mays</i> L. cv. Bari-7)

Abstract: NaCl salinity in the range of 50 to 200 mM increased Na+ accumulation in the root and shoot of 7-, 14- and 21-day-old maize seedlings. The accumulation of Na+ and Cl- increased but K+ accumulation decreased with the increase in NaCl concentration from 50 to 200 mM in the root and shoot of maize in all the three ages. Key words: Salinity, NaCl, Ion transport, Root, Shoot, Maize doi:10.3329/bjb.v37i2.1733 Bangladesh J. Bot. 37(2): 203-205, 2008 (December)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Regarding root length results were in accordance with the findings of the Khatoon et al (2010). Findings about Na + and K + ions results were in accordance with the findings of Ashrafuzzaman et al (2000), Irshad et al (2000), Gopal and Dube (2003), Karmoker et al (2008), Tas and Basar (2009) and Carpici et al (2009).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding root length results were in accordance with the findings of the Khatoon et al (2010). Findings about Na + and K + ions results were in accordance with the findings of Ashrafuzzaman et al (2000), Irshad et al (2000), Gopal and Dube (2003), Karmoker et al (2008), Tas and Basar (2009) and Carpici et al (2009).…”
Section: Discussionsupporting
confidence: 89%
“…Accumulation of Cl in the tissue is disruptive to membrane uptake mechanisms (Yousif et al, 1972). The reduction in potassium in shoots as result of salt stress (Table 3) has been observed previously, interpreted as resulting from competition between this ion and Na (Karmoker et al, 2008;Turan et al, 2010). According to Cordovilla et al (1995), NaCl decreased N concentration in the shoot tissues and the salinity has a negative impact on the nitrogen acquisition and utilization (Lewis, 1986).…”
Section: Discussionmentioning
confidence: 57%
“…There is non-significant effect of neomycine on Na + accumulation in shoot and root In this experiment, K + and Ca 2+ accumulation was decreased due to salinity as observed in mungbean plants (Haleem and Mohammed, 2007;Huo et al, 2015) and barley (Othman et al, 2006). Reduction in K + level resulted in reduced growth by decreasing osmotic adjustment and turgor maintenance as observed in maize (Karmoker et al, 2008) as well as in rice plants (Sakamoto and Murata, 2001). Results of this experiment indicated that PLC is involved in K + and Ca 2+ accumulation as observed with the significant effect of exogenous application of neomycine.…”
Section: Discussionmentioning
confidence: 60%